Relationship Between Cognitive Impairment and Depression Among Middle Aged and Older Adults in Primary Care - Alex D. Federman MD, MPH; Jacqueline Becker PhD; Fernando Carnavali MD; Monica Rivera Mindt PhD; Dayeon Cho MPH; Gaurav Pandey PhD; Lili Chan MD; Laura Curtis PhD; Michael S. Wolf PhD; Juan P. Wisnivesky MD, DrPH (Gerontology and Geriatric Medicine, 2024)
Objectives: To determine rates of previously undetected cognitive impairment among patients with depression in primary care. Methods: Patients ages 55 and older with no documented history of dementia or mild cognitive impairment were recruited from primary care practices in New York City, NY and Chicago, IL ( n  = 855). Cognitive function was assessed with the Montreal Cognitive Assessment (MoCA) and depression with the Patient Health Questionnaire-8. Results: The mean age was 66.8 (8.0) years, 45.3% were male, 32.7% Black, and 29.2% Latinx. Cognitive impairment increased with severity of depression: 22.9% in persons with mild depression, 27.4% in moderate depression and 41.8% in severe depression ( p  = .0002). Severe depression was significantly associated with cognitive impairment in multivariable analysis (standardized β = −.11, SE  = 0.33, p  < .0001). Discussion: Depression was strongly associated with previously undetected cognitive impairment. Primary care clinicians should consider screening, or expand their screening, for both conditions.